2017
DOI: 10.1111/ajt.14379
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Alleged Kidney Donor Profile Index Labeling Effect on Kidney Utilization

Abstract: The Kidney Donor Profile Index (KDPI) became a driving factor in deceased donor kidney allocation on December 4, 2014, with the implementation of the kidney allocation system (KAS). On April 20, 2016, the annual recalibration of the Kidney Donor Risk Index into KDPI was incorrectly programmed in DonorNet, resulting in erroneously high KDPI values, by between 1 and 21 percentage points (e.g. actual KDPI of 70% was displayed as 86%). The error was corrected on May 19, 2016, <24 h after being recognized. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…It improves to 0.78 (considered good discriminatory power) when comparing donors with the highest and lowest 20% estimated graft survival, supporting these categories of stratification for allocation . There is, however, a concern that labelling kidneys, ‘high KDPI’ will increase non‐utilization rates and compromise overall utility . Similarly, the c‐statistic for EPTS is 0.69, which has been externally validated in Australia and New Zealand .…”
Section: Utilitymentioning
confidence: 84%
“…It improves to 0.78 (considered good discriminatory power) when comparing donors with the highest and lowest 20% estimated graft survival, supporting these categories of stratification for allocation . There is, however, a concern that labelling kidneys, ‘high KDPI’ will increase non‐utilization rates and compromise overall utility . Similarly, the c‐statistic for EPTS is 0.69, which has been externally validated in Australia and New Zealand .…”
Section: Utilitymentioning
confidence: 84%
“…Examining changes in the kidney nonutilization rate after the introduction of KDPI use in the United States, Bae et al found that although there was no overall increase in the nonutilization rates, among kidneys that were previously labeled as “standard criteria” that were reclassified as “high risk” (KDPI > 85%) there was a significant increase in odds of nonutilization (adjusted OR [aOR]1.42, 95% CI 1.07 to 1.89, P = .02). In an opportunistic study, Stewart et al reported on the impact of KDPI labeling when the index was incorrectly calculated for a 30‐day period in the United States as the result of a programming error, resulting in erroneously high KDPI values being displayed with organ offers. During this period, the kidney nonutilization rate did increase, but not to the degree that would have been predicted based on the usual relationship between KDPI and organ nonutilization.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised about the potential labeling effect of KDPI reporting in Australia—that clinicians may be more reluctant to accept offers of kidneys with high KDPI, resulting in resource wastage in donation coordinator time to allocate kidneys and potentially even increased organ nonutilization. Similar issues have been debated in the United States after the introduction of KDPI use in the Kidney Allocation System . It is also possible that increased awareness of kidney quality at the time of organ offer will result in more discerning use of marginal kidneys and directed use of lower‐KDPI kidneys, resulting in improved matching between predicted recipient survival and predicted organ survival.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The error, which was introduced in 2016 when UNOS updated the KDPI calculator, resulted in a sharp rise in discard rate for deceased‐donor kidneys with an inflated KDPI that crossed the 85% policy threshold. Dr. Segev feels that this costly error should never have occurred …”
Section: The Criticismsmentioning
confidence: 99%